2016
DOI: 10.1111/jphp.12659
|View full text |Cite
|
Sign up to set email alerts
|

Chronic restraint stress increases angiotensin II potency in the rat carotid: role of cyclooxygenases and reactive oxygen species

Abstract: Stress increases AngII potency in rat carotid by a mechanism that involves the increased generation of PGI and H O and the activation of Akt pathway. Such mechanism could play a pathophysiological role in cardiovascular diseases correlated with stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Mental stress can induce NOX activation in the endothelium of thoracic aorta [ 63 ] and increase the expression of NOX-4 in carotid [ 64 , 65 ]. This study shows the NOX activation in the brain vessels and the expression of NOX subunits in mRNA and protein levels upon mental stress.…”
Section: Discussionmentioning
confidence: 99%
“…Mental stress can induce NOX activation in the endothelium of thoracic aorta [ 63 ] and increase the expression of NOX-4 in carotid [ 64 , 65 ]. This study shows the NOX activation in the brain vessels and the expression of NOX subunits in mRNA and protein levels upon mental stress.…”
Section: Discussionmentioning
confidence: 99%
“…The relative isoform selectivity renders this compound a useful tool (when a relatively low concentration of ML171 is employed) to elucidate the contribution of Nox1 to redox-signaling. For example, a recent study on the effects of chronic restraint stress on vascular function showed that ML171 (0.5 μM) reduced AngII-initiated vasoconstriction in rat carotid arteries in the presence and absence of endothelium, implying that Nox1-derived ROS positively influence AngII-mediated contraction in carotid arterial smooth muscle cells [237]. Another study comparing endothelial function of coronary arteries from male and female pigs reported that 100 μM ML171 enhanced bradykinin-induced endothelium-dependent relaxation in male rather than female porcine coronary arteries [238].…”
Section: Nox Inhibitors As Therapeutics For Microvascular Diseasesmentioning
confidence: 99%
“…Causal involvement of RAAS activity is supported by beneficial effects of ramipril and losartan. Chronic stress may excessively activate the RAAS (544) and increase arterial sensitivity to angiotensin (545). Chronic elevations in angiotensin II also induce inflammation, endothelial dysfunction and senescence (546, 547), while angiotensin receptor antagonism protects against the effects of chronic stress (548).…”
Section: Chronic Stress Modifies Vascular Function and Structure And ...mentioning
confidence: 99%